Spin-transfer effect and its use in spintronic components. (22nd February 2010) - Dieny, B.; Sousa, R.C.; Herault, J.; Papusoi, C.; Prenat, G.; Ebels, U.; Houssameddine, D.; Rodmacq, B.; Auffret, S.; Buda-Prejbeanu, L.D.; Cyrille, M.C.; Delaet, B.; et al.
Spin-electronics is a very rapidly expanding area of R&D which merges magnetism and electronics (Nobel Prize 2007). Since the discovery of giant magnetoresistance in 1988, several breakthroughs have further boosted this field (spin-valves 1990, tunnel magnetoresistance 1995, spin transfer 1996, voltage controlled magnetic properties 2004). The phenomenon of spin-transfer is particularly attractive both from fundamental and applied view points. It provides a new way to manipulate the magnetisation of magnetic nanostructures by a spin-polarised current. Spinelectronics has found applications in hard disk drives (1998) and more recently in non-volatile standalone memories (MRAM = Magnetic Random Access Memory). The spin-transfer phenomenon provides a new write scheme in MRAM yielding a much better scalability of these devices towards the 22 nm node. Furthermore, besides MRAMs, hybrid CMOS/magnetic technology can yield a totally new approach in the way electronic devices are designed. Most CMOS devices such as microprocessors are based on Von Neumann architecture in which logic and memories are separate components. The unique set of characteristics combined within magnetic tunnel junctions: cyclability, switching speed, scalability, makes it possible to conceive novel electronic systems in which logic and memory are intimately combined in non-volatile logic components (concept of non-volatile CPU). The spin-transfer phenomenon can also be used to generate large amplitude steady magnetic excitations in magnetic nanostructures. This phenomenon can also be used to conceive new frequency tunable radiofrequency oscillators. The latter are very attractive for wireless applications which require scanning large frequency bandwidth.